(untitled) (The Research of Medical Science Review, 2024)
BACKGROUND: Obstructive uropathy is common and requires immediate treatment to prevent renal damage. Double-J (DJ) stent placement and percutaneous nephrostomy (PCN) are two common treatments for this condition, but they have different complications that may affect patient outcomes and intervention choice. This study compares DJ stent and PCN complication rates in urolithiasis-related obstructive uropathy patients to determine their safety and efficacy.METHODOLOGY: This randomised control trial was conducted at SIUT, Karachi included 296 18-65-year-olds with obstructive uropathy due to urolithiasis and stones larger than 1 cm. Randomisation divided patients into DJ stent (n=148) and PCN (n=148) groups. Prophylactic antibiotics were given to all patients after cystoscopic DJ stent insertion and ultrasound-guided PCNs. Haematuria, procedural failure, fever, trigone irritation, and PCN dislodgement were monitored for 7 days. Statistical analysis compared group complication rates.RESULTS : The mean age was of the patients were 42.10±14.61 year in the DJ stent group and 40.36±13.69 years in the PCN group, with males representing 74.8% and 71.0% of each group, respectively. Procedural failure rates between groups were (3.7% in DJ stent vs 2.8% in PCN, p=0.500). Fever & septicemia documented in 8.4% of the DJ stent group and 4.7% of the PCN group (p=0.269), whereas hematuria was noted in 12.1% of DJ stent patients and 6.5% of PCN patients (p=0.159). Painful trigone irritation was significantly higher in the DJ stent group (15.0% vs. 0%, p=0.0001). PCN-specific complications, such as dislodgement or blockage, were found in 5.6% of the PCN group, with no cases in the DJ Stent group (p=0.015).CONCLUSION: It is to be concluded that both DJ stent and PCN are effective in managing obstructive uropathy secondary to urolithiasis, with similar rates of procedural failure, hematuria, & fever, however, DJ stents are linked with significantly higher rates of painful trigone irritation while PCN shows a unique chance of dislodgement or blockage. These findings recommend that the choice between DJ stent and PCN should consider the distinct complication profiles of each method to optimize the patient outcomes.